Peningkatan Keterampilan Desain Visual Digital Berbasis Canva Pada Remaja Karang Taruna RT 04 Perumahan Tjitramas Residence - Dwi Yulistyanti; Naely Farkhatin; Ulfa Pauziah; Aulia Paramita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This activity aims to improve digital visual design skills among youth members of Karang Taruna RT 04, Tjitramas Residence, through the use of the Canva application. The background of this activity is the limited ability of youth in creating attractive and informative visual content for social media. The method used is action research with a mixed-method approach, consisting of planning, implementation, observation, and reflection stages. The participants consisted of 25 youths who attended the training through material presentation, demonstrations, and hands-on design practice. Data collection techniques included observation, pre-test and post-test, and evaluation of participants’ work using a rubric-based assessment instrument. The results indicate an improvement in participants’ skills in using Canva, including feature understanding, creativity, layout arrangement, and relevance to the given theme. Most participants were able to produce visual designs suitable for social media publication such as posters, promotions, logos, social media content, and marketing materials independently.In conclusion, this training is effective in enhancing youth digital design skills and can serve as a medium for creativity development and promotion of community activities.